1999
DOI: 10.1136/adc.81.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and growth failure in cyanotic and acyanotic congenital heart disease with and without pulmonary hypertension

Abstract: Aim-To investigate the eVect of several types of congenital heart disease (CHD) on nutrition and growth. Patients and methods-The prevalence of malnutrition and growth failure was investigated in 89 patients with CHD aged 1−45 months. They were grouped according to cardiac diagnosis: group aP (n = 26), acyanotic patients with pulmonary hypertension; group ap (n = 5), acyanotic patients without pulmonary hypertension; group cp (n = 42), cyanotic patients without pulmonary hypertension; and group cP (n = 16), cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
194
5
20

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 14 publications
18
194
5
20
Order By: Relevance
“…According to literature, among cyanotic patients, those patients with pulmonary arterial hypertension were the most severely affected with weight delay 13 . Evidences show, without classifying patients in cyanotic or non-cyanotic congenital heart disease, that height and weight at birth and during this study and height and weight growth of patients with congenital heart disease were lower when compared to healthy children 2 .…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, among cyanotic patients, those patients with pulmonary arterial hypertension were the most severely affected with weight delay 13 . Evidences show, without classifying patients in cyanotic or non-cyanotic congenital heart disease, that height and weight at birth and during this study and height and weight growth of patients with congenital heart disease were lower when compared to healthy children 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Varan et al, in their study in children with cyanotic and acyanotic CHD in 1996-1997, reported that 65% of the children were below the 5 th percentile for weight, and 41% were below the 5 th percentile for both weight and height. 9 In the early 1930s, an expanding body of literature documented bacteremia after a wide variety of dental procedures, including tooth brushing and chewing, in uninfected mouths. 10,11 Prophylaxis is particularly important for children because endocarditis is still associated with high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased caloric intake has been shown to be the most important cause of malnutrition in pediatric patients with CHD [7]. A study published by Hansen and Dorup [8] showed that caloric intake in patients with CHD was 76% that of normal age-matched controls.…”
Section: Inadequate Energy Intakementioning
confidence: 99%